PERCEPTION OF QUALITY OF LIFE AND LEVEL OF PHYSICAL ACTIVITY IN URBAN BUS DRIVERS IN THE CITY OF ARACAJU/SE (Fiep Bulletin - online, 2011)
The improvement of living conditions and health of workers has been a topic of growing importance in the occupational sector as direct or indirect impacts on productivity and health of employees. This study characterized as descriptive correlational cross aimed to analyze the quality of life and their relationship with physical activity level of urban bus drivers in the city of Aracaju, Sergipe, Brazil. The sample consisted of 322 drivers selected in a representative and that were willing to voluntarily participate in the study. Was applied the WHOQOL-bref and QIAF in its shortened version. The results showed prevalence of 77% in the range of risk related to inactivity, 52% with negative perception of the quality of life, 28% with negative perception of health, the areas physical, psychological and social were in "good", however the field of the environment had to "adjust" to the group and, the variable domains of physical, psychological and environment have to be related with the level of physical activity. It was concluded that regular physical activity is related to the perception of quality of life and health in the sample studied.
Keywords: Quality of life; Physical Activity; Bus drivers